The utility of vertebral Hounsfield units as a prognostic indicator of adverse events following treatment of spinal epidural abscess - Alexander M. Crawford, MD, MPH; Brendan M. Striano, MD, MPH; Ikechukwu C. Amakiri, MD, MBA; Donnell L. Williams, BS; Matthew H. Lindsey, MD; Jonathan Gong, BS; Andrew K. Simpson, MD, MBA, MHS; Andrew J. Schoenfeld, MD, MSc (North American Spine Society Journal, 2024)
ABSTRACT: Background: Spinal epidural abscesses (SEAs) are a devastating condition with high levels of associated morbidity and mortality. Hounsfield units (HUs), a marker of radiodensity on CT scans, have previously been correlated with adverse events following spinal interventions. We evaluated whether HUs might also be associated with all-cause complications and/or mortality in this high-risk population. Methods: This retrospective cohort study was carried out within an academic health system in the United States. Adults diagnosed with a SEA between 2006 and 2021 and who also had a CT scan characterizing their SEA within 6 months of diagnosis were considered. HUs were abstracted from the 4 vertebral bodies nearest to, but not including, the infected levels. Our primary outcome was the presence of composite 90-day complications and HUs represented the primary predictor. A multivariable logistic regression analysis was conducted adjusting for demographic and disease-specific confounders. In sensitivity testing, separate logistic regression analyses were conducted (1) in patients aged 65 and older and (2) with mortality as the primary outcome. Results: Our cohort consisted of 399 patients. The overall incidence of 90-day complications was 61.2% (n=244), with a 7.8% (n=31) 90-day mortality rate. Those experiencing complications were more likely to have undergone surgery to treat their SEA (58.6% vs. 46.5%; p=.018) but otherwise the cohorts were similar. HUs were not associated with composite 90-day complications (Odds ratio [OR] 1.00 [95% CI 1.00—1.00]; p=.842). Similar findings were noted in sensitivity testing. Conclusions: While HUs have previously been correlated with adverse events in certain clinical contexts, we found no evidence to suggest that HUs are associated with all-cause complications or mortality in patients with SEAs. Future research hoping to leverage 3-dimensional imaging as a prognostic measure in this patient population should focus on alternative targets. Level of Evidence: Level III; Observational Cohort study.